One crisis, different paths to supply resilience: The case of ventilator procurement for the COVID-19 pandemic. Issue 5 (December 2022) - Dube, Nonhlanhla; Li, Qiujun; Selviaridis, Kostas; Jahre, Marianne
Abstract: This research explores supply resilience through an equifinality lens to establish how buying organizations impacted differently by the same extreme event can strategize and all successfully secure supply. We conduct case study research and use secondary data to investigate how three European governments sourced for ventilators during the first wave of COVID-19. The pandemic had an unprecedented impact on the ventilator market. It disrupted already limited supply and triggered a demand surge. We find multiple paths to supply resilience contingent on redundant capacity and local sourcing options at the pandemic's onset. Low redundancy combined with limited local sourcing options is associated with more diverse strategies and flexibility. The most notable strategy is spurring supplier innovation by fostering collaboration among actors in disparate industries. High redundancy combined with multiple local sourcing options is associated with more focused strategies and agility. One (counter-intuitive) strategy is the rationalization of the supply base. Highlights: Buying organisations manage risks related to extreme events differently. Buying organisations are not equally vulnerable to the same event's effects. Suitable responses depend on each organisation's vulnerability when an event occurs. Supply resilience is achieved by aligning response strategies with vulnerability. Overall, this implies different paths to supply resilience to the same event.